PENDUGAAN POTENSI AIR TANAH MENGGUNAKAN METODE GEOLISTRIK DI TEMPAT WISATA RAMMANG-RAMMANG KECAMATAN BONTOA KABUPATEN MAROS - Hamzah, Hamzah; Invanni, Ichsan; Badwi, Nasiah (UNIVERSITAS NEGERI MAKASSAR, 2020)
Electrical Resistivity is one of the geophysical methods that can detect the flow of electricity below the earth’s surface. This study aims to determine subsueface lithology, determine the potential of groundwater and determine the location of prospective drill sumut placement in the tourist attractions of Rammang-Rammang, Bontoa District, Maros Regency. This research uses electrical resistivity method with Wenner and Schlumberger configuration. Processing data using Res2DinV to map subsurface 2d isoresistivity. From the results of this study the resistivity value is different for each rock starting from 2,36 – 40434 Ωm the resistivity value of fresh water is in the range of resistivity value 30 -100Ωm. Subsuface lithology in the area namely alluvial, limestone, hollow limestone and limestone with massive structure.From the interpretation of the measurement data made at the study site, the location of the prospective well bore for drilling is located at coordinates, trajectory 1 119036'37.154